Determining risk factors for surgical wound dehiscence: Development and internal validation of a risk assessment tool - Sandy-Hodgetts, Kylie Michelle (Curtin University, 2018)
Whilst surgical procedures are considered safe, complications such as surgical wound dehiscence (SWD) may occur despite advances in surgical techniques, infection control practices and wound care. A SWD risk assessment tool was developed from identified risk factors based on a review of the literature and a retrospective case control study. A prospective clinical validation of the tool yielded a predictive power of 71% with an interrater reliability of 100%.